Media, technology, and literacy in immigrant and multicultural contexts - David F. Hemphill; Sally L. Ianiro; Damien A. Faffa (Adult Education Research Conference, 1995)
The impacts of electronic media on literacy, language, and cultural knowledge among immigrant and multicultural youths and adults in a diverse urban setting are addressed. We analyze electronic media consumption in terms of preferred forms and genres, social functions, support for maintenance of cultural identity, and education and information functions, concluding that media perform complex and unique functions for marginalized adult learner populations that merit much more serous consideration for adult basic education policy and curricula than they currently receive.